Editorial: Resilience of Local Communities – The United Nations Perspective - Meško, Gorazd (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
Resilience in the local environment is reflected in the efforts of the United Nations within the framework of all the Sustainable Development Goals, and in particular in the goal that focuses on sustainable cities and communities. The research programme Safety and security in local communities has been focusing on various aspects of safety and security in local communities since 2015. Over the ten-year period, we have organised six international conferences, eight international student conferences and ten national conferences, where we connected theory with practice and learned about Slovenian local communities. This year's eleventh conference begins with a round table on resilience in local communities, followed by presentations of contributions from the field of resilience of local communities, presenting important perspectives on security and the quality of life of people in local environments.